Mycoherbicides for the Noxious Meddlesome: Can Colletotrichum be a Budding Candidate? - Chakraborty, Anwesha; Ray, Puja (Frontiers in Microbiology, 2021)
Invasive plant species are a major threat to biodiversity and agricultural productivity. Hence efforts to manage these menace involves extensive and effective use of chemical herbicides among others. However not-only is the impact of control with chemical herbicides short-lived but also leads to negative impact on human health and environment due to non-target herbicide-drift and runoff from the sprayed areas. This has ushed in a much-anticipated nature-based potential regulators of weed species, in an attempt to lower the utilization of chemical herbicides. Mycoherbicides have been seen as a benign, eco-friendly, host-specific, replacement for chemical herbicides. There are several noteworthy genera of fungus that have been proved to be effective against weeds. They either produce strong phytotoxins or are often used as spore/ conidia-based solutions and applied as a spray in growth media. One of such potential genera is Colletotrichum Corda 1831. Compared to other potent fungal genera, with well-established roles in conferring herbicidal activities by producing competent phytotoxins, only a few species under genus Colletotrichum are known to produce fungal metabolites be used as phytotoxins. This article elucidates the current understanding of using spore suspension/ phytotoxin of Colletotrichum as a weedicide. We also discuss the interaction between fungal metabolites release and Colletotrichum- target plant, from a molecular and biochemical point of view. This review article has been written to accentuate on the potency of Colletotrichum, and to serve as an eye-opener to consider this genus for further fruitful investigations. However inconsistency associated with mycoherbicides in terms of viability and efficacy under field conditions, production of bioactive compound, slow natural dispersal ability, etc, have often reduced their utility. Hence our study emphasizes on the need to do extensive research in elucidating more phytotoxins from necrotrophic phytopathogenic microorganisms with novel mode of action for field application.